PENGARUH PARTISIPASI PENYUSUNAN NAGGARAN, PENGAWASAN FUNGSIONAL, KOMITMEN ORGANISASI DAN GAYA KEPEMIMPINAN TERHADAP KINERJA PEMERINTAH DAERAH (Studi Empiris Pada Organisasi Perangkat Daerah Kabupaten Pelalawan) - Lutfiandri Miki; Nasrizal Nasrizal; Putra Agri Adhitya (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2020)
This research was conducted in Pelalawan Regency, Riau Province. The purpose of this study was to test empirically the effect of budgetary participation on the performance of local government agencies (P1) To empirically test the effect of functional supervision on the performance of local government agencies (P2) To test empirically the effect of organizational commitment on the performance of local government agencies (P3) To test empirically the effect of leadership style on the performance of local government agencies (P4). This research is expected to be useful as information material for readers and reference material for interested parties in an effort to improve the performance of a local government agency. The type of data used in this study is primary data. And by using the empirical study method. The variables in this study are Participation in Budgeting (P1) Functional Monitoring (P2) Organizational Commitment (P3) Leadership Style (P3). From the research that has been done, it is found that 1) The results of testing the first hypothesis indicate that budgetary participation affects the performance of the Pelalawan Regency local government. 2) The results of testing the second hypothesis show that functional supervision has no effect on the performance of the Pelalawan district government. 3) The results of testing the third hypothesis that organizational commitment has no effect on the performance of the Pelalawan district government. 4) The results of testing the fourth hypothesis, the leadership style has no effect on the performance of the Pelalawan district government.Keyword: Participation, Supervision, Commitment, Leadership Style; Local Government Performance.